The Effect of Student Satisfaction and Learning Environment on The Academic Achievement of Students of Perdana Vocational High School 1 Surabaya - Maria Melania Jaisa; Tutik Winarsih (STIE Amkop Makassar, 2026)
This study analyzes the influence of learning satisfaction and learning environment on the academic achievement of students at Perdana 1 Vocational High School Surabaya. The background of this study is the growing importance of non-cognitive factors in shaping student performance. A quantitative survey was conducted with 90 participants, and the data were examined using validity and reliability assessments, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. All instruments were found to be valid and reliable, with Cronbach’s Alpha values exceeding 0.70. The classical assumption tests indicated that the data were normally distributed, free from multicollinearity, and did not exhibit heteroscedasticity. Regression analysis revealed that both independent variabel have a positive significant effect on academic achievement, with the learning environment identified as the most dominant influencing factor. The simultaneous test confirmed a significant combined effect of both variables on academic achievement with a significance value of 0.000 < 0.05. Furthermore, the coefficient of determination (R² = 0.668) indicates that 66.8% of the variation in academic achievement can be explained by learning satisfaction and learning environment. These findings suggest that improving learning satisfaction and creating a conducive learning environment are key strategies to enhance student academic achievement.